A Feasibility study om Sorbiwood Interior Wood Trims - Aquitania, Aries Alexander E.; Cuerda, Kristine Rose L.; De Ocampo, Leon Francis R.; Gosiengfiao, Alan C. (College of Engineering, 1997)
Sorbiwood interior wood trims offer a chance to "revolutionize" the wood industry in the Philippines. It uses a patented manufacturing technology that can compress fibrous materials with bonding agents to create products that are as strong as wood, but costs far less. The product has several advantages: it can be more readily impregnated with preservatives, easier to glue than solid wood, has good sound absorption, and is cheaper than solid wood and MDF. The product shall be offered 20% lower than the average market price. The plant shall employ a major investor to market its products to the target customers. As determined by the market study, the project is feasible with an annual market share growth of 10% from an initial share of 15.07% of the market. These figures were garnered from its potential target market namely the contractors, architects, interior designers, and do-it-yourself builders. The technical aspect of the project showed favorable results as well. The plant shall be located in a 1,000 sq.m plant in Mexico, Pampanga, and shall employ a total of 19 personnel. Production will be on a daily basis, 8 hours a day, 260 days a year. Therefore, only one shift will be allotted a day and it is expected to produce an average of 537 bars a day for the first year. Supervision of plant operations shall be done by the general manager and the plant supervisor. Financially, the company shall be owned and managed by a group of investors from Simmons, Inc., and shall be registered under the name of Sorbiwood, Inc. There are other sources of financing the project as well. After evaluating possible sources of financing, the most appealing institution is the Development Bank of the Philippines. The total project cost amounts to P19,577,544.00. The company can borrow a maximum of P1,374,343.62, or 7.02% of the total project cost. The project provides its owners ample time to pay its debt within the 5-year period, projecting the payback period at 4.38 years. Also, the financial analysis illustrates an attractive NPV (P1,778,638.39) and IRR (24.80%) indicating a profitable position of the project. The organizational and management analysis merely mentions that the company will be a corporation with a total of 19 personnel. IT will have and administrative staff consisting of the general manager, an executive assistant, a production supervisor, an accountant and a clerk. Furthermore, its production workforce will be composed of 5 equipment operators, 5 helpers and 2 utility men. To maintain security, Sorbiwood, Inc. will acquire 2 security personnel. The social profitability analysis exemplifies the unparalleled benefits the product will bring the society. To be exact, Sorbiwood interior wood trims will improve the standard of living, contribute to the betterment and development of the community, encourage the lowering of prices of interior wood trims, and utilize local materials and wastes. Moreover, its sales will be a positive contribution to the National Economy. After evaluating the data gathered, the Sorbiwood interior wood trims is feasible.